IMPLEMENTASI TEKNIK FAILOVER RECURSIVE GATEWAY - Tohirin Al Mudzakir; Adi Rizky Pratama; Ayu Ratna Juwita (BUANA ILMU, 2023)
The development of information technology and the internet in Indonesia every year shows very rapid progress in terms of reliable infrastructure, users, hardware, software and information systems. At Buana Perjuangan University, Karawang has two internet lanes designated for users of all academics, both LAN and wifi, and one more lane for servers. These conditions sometimes create problems when one of the internet lines is down which results in hampering service activities. Based on the background above, the authors propose the implementation of a Failover Recursive Gateway, with the aim that there will be no more cessation of administrative services when one of the internet lines is down.